Budesonide Orodispersible Tablets Maintain Remission in a Randomized, Placebo-Controlled Trial of Patients With Eosinophilic Esophagitis - Straumann, Alex; Lucendo, Alfredo J.; Miehlke, Stephan; Vieth, Michael; Schlag, Christoph; Biedermann, Luc; Vaquero, Cecilio Santander; Ciriza de los Rios, Constanza; Schmoecker, Christoph; Madisch, Ahmed; Hruz, Petr; Hayat, Jamal; et al. (Gastroenterology, 2020)
Background & Aims: Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder. Swallowed topical-acting corticosteroids are effective in bringing active EoE into remission. However, it is not clear whether these drugs are effective for long-term maintenance of remission. Methods: We performed a double-blind trial to compare the efficacy and safety of 2 dosages of a budesonide orodispersible tablet (BOT) vs placebo in maintaining remission of EoE. Maintenance of remission was defined as absence of clinical and histologic relapse and no premature withdrawal for any reason. Two hundred and four adults with EoE in clinical and histologic remission, from 29 European study sites, were randomly assigned to groups given BOT 0.5 mg twice daily (n = 68), BOT 1.0 mg twice daily (n = 68), or placebo twice daily (n = 68) for up to 48 weeks. Results: At end of treatment, 73.5% of patients receiving BOT 0.5 mg twice daily and 75% receiving BOT 1.0 mg twice daily were in persistent remission compared with 4.4% of patients in the placebo group (P < .001 for both comparisons of BOT with placebo). Median time to relapse in the placebo group was 87 days. The frequency of adverse events was similar in the BOT and placebo groups. Morning serum levels of cortisol were in the normal range at baseline and did not significantly change during treatment. Four patients receiving BOT developed asymptomatic, low serum levels of cortisol. Clinically manifested candidiasis was suspected in 16.2% of patients in the BOT 0.5 mg group and in 11.8% of patients in the BOT 1.0 mg group; all infections resolved with treatment. Conclusions: In a phase 3 trial, up to 48 weeks of treatment with BOT (0.5 mg or 1.0 mg twice daily) was superior to placebo in maintaining remission of EoE. Both dosages were equally effective and well tolerated. EudraCT number; 2014-001485-99; ClinicalTrials.gov number, NCT02434029.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Dysphagia; Patient-Reported Outcomes; Remission; Topical Corticosteroids